EFFECT OF SOME PLANT EXTRACT AND ANTIBIOTIC ON Cucumber Mosaic Cucumovirus - N.A. Kassim (Mesopotamia Journal of Agriculture)
Purified caffeine showed the best efficiency in the inhibiting the infection caused by CMV in vitro, when mixed its solution with crude sap of infected plant, followed by the extraction of dried flower of carnation, then by tea extraction, by using Chenopodium amaranticolor as indicator plant, while the antibiotic, chloramphenicol showed the best inhibiting effect on this virus in vitro, then followed by penicillin, but mercurochrome did not showed any effect on CMV. The extractions of carnation flower, caffeine and tea showed inhibiting effect on CMV in vivo, chloramphenicol also inhibited CMV in vivo, whereas penicillin and mercurochrome did not showed any inhibition effect on this virus.